Nonsense-mediated mRNA decay modulates Arabidopsis flowering time via the SET DOMAIN GROUP 40–FLOWERING LOCUS C module. (16th July 2021) - Nasim, Zeeshan; Fahim, Muhammad; Hwang, Hocheol; Susila, Hendry; Jin, Suhyun; Youn, Geummin; Ahn, Ji Hoon
Abstract: The nonsense-mediated mRNA decay (NMD) surveillance system clears aberrant mRNAs from the cell, thus preventing the accumulation of truncated proteins. Although loss of the core NMD proteins UP-FRAMESHIFT1 (UPF1) and UPF3 leads to late flowering in Arabidopsis, the underlying mechanism remains elusive. Here, we showed that mutations in UPF1 and UPF3 cause temperature- and photoperiod-independent late flowering. Expression analyses revealed high FLOWERING LOCUS C ( FLC ) mRNA levels in upf mutants; in agreement with this, the flc mutation strongly suppressed the late flowering of upf mutants. Vernalization accelerated flowering of upf mutants in a temperature-independent manner. FLC transcript levels rose in wild-type plants upon NMD inhibition. In upf mutants, we observed increased enrichment of H3K4me3 and reduced enrichment of H3K27me3 in FLC chromatin. Transcriptome analyses showed that SET DOMAIN GROUP 40 ( SDG40 ) mRNA levels increased in upf mutants, and the SDG40 transcript underwent NMD-coupled alternative splicing, suggesting that SDG40 affects flowering time in upf mutants. Furthermore, NMD directly regulated SDG40 transcript stability. The sdg40 mutants showed decreased H3K4me3 and increased H3K27me3 levels in FLC chromatin, flowered early, and rescued the late flowering of upf mutants. Taken together, these results suggest that NMD epigenetically regulates FLC through SDG40 to modulate flowering time in Arabidopsis. Abstract : The nonsense-mediated decay RNA surveillance system regulates the levels of a histone methyltransferase, which modifies the chromatin status of a gene that represses flowering, modulating flowering time.